Correlation between Degree of Compliance to Antihypertensives with Severity of Stroke - Hirra Mumtaz; Ramish Riaz; Haris Majid Rajput; Anum Akhtar (KARACHI MEDICAL AND DENTAL COLLEGE, 2018)
Objective: Study was conducted to find out correlation between degree of  compliance  to  antihypertensives with severity of stroke. Methods: This correlational study was conducted in department of neurology,  Pakistan  Institute  of  Medical Sciences, Islamabad from December 2017 to  May  2018. A total  of  74  patients  with  clinically and radiologically confirmed diagnosis of stroke, having history of hypertension, were  included  in  the study. According to the Modified Rankin Scale (MRS), scores were assigned from 0 to 6 in increasing    order of severity. Quantitative assessment to drug compliance was calculated via Brief Adherence Rating Scale (BARS). According to BARS, scores were assigned from 1 to 4 in decreasing order of non-compliance or increasing order  of  compliance.  Compliance  was  defined  according  to  BARS  as  patients taking more  than  76%  of  their  prescribed  dosage.  Compliance  of  drug  was  checked  for last 6 months. Data was finally analysed by SPSS v. 20. Appropriate statistical tests were applied. Results: Mean age of the stroke patients was 58.8 ± 14.91 years. Total 33 patients i.e. 44.6% were compliant and 41 were noncompliant. Strong negative correlation (r= -0.494,  p-value=  0.00008)  was  found between degree of compliance according to BARS  scale  and  severity  of  stroke  according  to  MRS. Regression analysis showed R2 value of 0.41  and  p-value  of  0.0004.  Most  common  cause  of drug noncompliance according to  patients  was  improper  counselling  followed  by  fear  of  getting  used to medication, forgetting, cost, side effects,  and  dissatisfaction  with  treatment.  Among  other  risk  fac- tors for stroke, 18.9% had positive history for smoking, 43.2% for hyperlipidaemia, 18.9% for coronary   artery disease, and 5.4% for atrial fibrillation. Conclusion: Adherence to antihypertensives can help in reducing severity of stroke which will result in better prognosis and reduced morbidity and mortality. Most important factor contributing to noncompliance is lack of awareness regarding disease and importance of antihypertensive medications.